Educating future accountants: a cross-curricular, flipped classroom approach to integrating global warming knowledge into an accounting curriculum - Hui Li; Jing Cui (Humanities & Social Sciences Communications)
Abstract Education has been identified as foundational in championing climate change action. Consequently, increasing efforts have been made to incorporate climate change knowledge into the curricula of predominantly non-environmental science-oriented subjects. However, in accounting instruction, attempts to integrate climate change have been largely prescriptive. This empirical study contributes to the literature by proposing a cross-curricular, flipped classroom approach that foregrounds group collaboration and local company research. Knowledge of global warming (GW) and local companies engaged in combating GW was gathered by 20 third-year accounting students, who were randomly divided into two teams. Based on this information, they were tasked with extracting financial data and using it to write a financial analysis report (FAR) for the selected companies. Meanwhile, qualitative and quantitative data were obtained from pre- and post-study questionnaires, the teams’ instant messaging exchanges, and the FAR assessment scores to evaluate whether the participants’ GW knowledge improved, whether they remained engaged and applied their accounting knowledge, and whether they had a strong perception of the GW knowledge gained and the methodology adopted. The results confirmed improvements in GW knowledge and demonstrated high engagement levels between the two teams. However, team-based differences were observed in the participants’ application of accounting knowledge, information-mining competencies, perceptions of challenges encountered, and recommendations for future studies. These findings have far-reaching implications for accounting instruction, collaborative teamwork, and institutional policies regarding the integration of climate change knowledge into existing curricula.